The Theological Importance of Differentiating Identities. National and Christian Identity in New Testament Light - Mørch, Michael Agerbo (2025)
The article argues for the theological importance of differentiating between identities. It presents the argument with a focus on the relationship between national and Christian identity. I begin by assessing why identity is such a controversial topic in today’s society. I then pay attention to how we should understand the complex concept of ‘identity’ before moving on to discuss national and Christian identity. While national identity is understood as a diffuse mixture of stability and plasticity, in the New Testament Christian identity is understood as distinctly stable and of an ontological nature. This view is demonstrated through a systematic reconstruction of the New Testament statements on identity, which concludes that the union with Christ in faith regenerates the believers and makes individuals part of the body of Christ, and that this is a fundamental change in identity. The dual aspects of regeneration and ecclesiology are identified as the centre of the New Testament understanding of identity. The article concludes by developing the concept of ‘differentiating identity’, seeking to describe the appropriate distinctions between different identities. Christian identity is here understood as so-called aspectival, while all other identities are understood as merely partitive.
Keywords: Identity; aspective identity; difference of identity; Ecclesiology; National Identity